Regulation Networks Driving Vasculogenic Mimicry in Solid Tumors - Hernández de la Cruz, Olga N.; López-González, José Sullivan; García-Vázquez, Raúl; Salinas-Vera, Yarely M.; Muñiz-Lino, Marcos A.; Aguilar-Cazares, Dolores; López-Camarillo, César; Carlos-Reyes, Ángeles (Frontiers in Oncology, 2020)
Vasculogenic mimicry (VM) is a mechanism in which cancer cells forms microvascular structures similar to 3D channels to provide nutrients and oxygen to tumors. Unlike angiogenesis, VM is characterized by the development of new patterned 3D vascular-like structures, independent of endothelial cells. This phenomenon has been observed in many types of highly aggressive solid tumors. The presence of VM also has been associated with increased resistance to chemotherapy, low survival, and poor prognosis of patients. The microRNAs (miRNAs) and long non-coding RNAs (lncRNAs) are non-coding RNAs that regulate gene expression at post-transcriptional level through different pathways. In recent years, it has been described that these tiny RNAs are expressed aberrantly in different human malignancies, thus contributing to hallmarks of cancer. In this context, miRNAs and lncRNAs can be excellent biomarkers for the diagnosis, prognosis, and prediction of response to therapy. In this review, we summarized the latest advances in VM regulation by miRNAs and lncRNAs in human cancers. We first provided an overview of the mechanisms of VM with examples in diverse types of tumors, and the role of tumor microenvironment and epithelial-mesenchymal transition in the development of VM. Finally we described the regulation networks of lncRNAs-miRNAs and their clinical impact with the VM.